Wine and Vine Components and Health - Rifler, Jean-Pierre (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
While there is a tremendous literature on the topic of wine and health ranging back to the days of Hippocrates, it is considered that there is an unlimited variety of wine, allowing for the association of senses, nutrition, and hedonism. The history of vine and wine has lasted for at least 7000 years. Vitis represent adaptable plants, and thanks to the large variety of strains, wine is an alchemical mix with unique properties, a rich and original composition in terms of polyphenols, and well known antioxidants. This explains why wine and health are closely linked to nutrition.